Direct current stimulation of prefrontal cortex modulates error‐induced behavioral adjustments. (13th June 2016) - Mansouri, Farshad A.; Fehring, Daniel J.; Feizpour, Azadeh; Gaillard, Alexandra; Rosa, Marcello G.P.; Rajan, Ramesh; Jaberzadeh, Shapour
Abstract: Commission of errors and conflict between choices might induce behavioral modulations through adjustments in the executive control of behavior and altered patterns of these modulations are detected in neuropsychiatric disorders. We examined the effects of transcranial Direct Current Stimulation (tDCS) applied over the dorsolateral prefrontal cortex (DLPFC) on error‐ and conflict‐induced behavioral modulations. Two separate cohorts of participants performed two clinically relevant tests of executive control, respectively. In the Wisconsin Card Sorting Test (WCST), the relevant rule for matching items frequently changed and therefore participants had to detect these unannounced changes by trial and error and alter their rule‐based behavior. In the Stop task, participants had to rapidly respond to a directional go‐signal but inhibit their responses when a stop signal appeared after the go‐signal. Each participant received tDCS (sham, cathodal or anodal) in three separate sessions. Errors led to a slower response in the next trial (post‐error slowing) in both tasks. The tDCS significantly modulated the post‐error slowing in both tasks but did not affect the behavioral adjustments induced by the conflict. The modulation of post‐error slowing by tDCS were polarity‐dependent and also trial specific appearing immediately after errors. In the WCST and Stop task, the post‐error slowing may reflect different processes involved in shifting the behavior‐guiding rule and adjustments in inhibitory control of responses, respectively, and we found that the effective tDCS polarity differed between the two tasks. Here, we show that in two separate cognitive tasks direct current stimulation of DLPFC significantly modulated error‐induced behavioral modulations. Abstract : In participants performing a computerized version of the Wisconsin Card Sorting Test and the Stop task, errors led to response slowing in the following trial (post‐error slowing). Post‐error slowing was significantly modulated by direct current stimulation of the dorsolateral prefrontal cortex.